Two new Cyphoderus (Collembola: Paronellidae) of “tridenticulati” and “bidenticulati” groups from Brazilian Amazon - Oliveira, João Victor L.c.; Alves, Jorge L.s.; Zeppelini, Douglas (Zootaxa, 2017)
Two new species of Cyphoderus Nicolet are described from northern Brazil: C. mucrominimus sp. nov. from Curionópolis, Pará; and C. mucrostrimenus sp. nov. from Parauapebas, Pará. These species belong to tridenticulati and bidenticulati groups respectively. The chaetotaxy of head and whole body are described and an identification key for the species with recorded distribution in Brazil is provided.